A Novel Cold-Mixed Epoxy Concrete and Its Comparison with Hot-Mixed Epoxy Asphalt Concrete - Kuan Li; Jianguang Xie; Youqiang Pan; Yanping Liu; Zhanqi Wang (Advances in Materials Science and Engineering)
A novel cold-mix epoxy (CME) concrete was developed to meet the urgent demand of quick maintenance in long-span steel deck pavement. Considering that the CME is a thermosetting resin, a differential scanning calorimeter (DSC) was employed to evaluate the curing behavior of the CME binder. Dynamic mechanical analysis (DMA) was used to investigate the viscoelasticity of the CME binder. The semicircular bending test and the three-point bending test were used to evaluate the crack resistance of CME concrete. Long-term performance was investigated by comparing the fatigue behavior of the CME concrete and hot-mixed epoxy asphalt (HMEA) concrete. The results showed that the curing reaction order of CME is similar to that of HME (hot-mixed epoxy) and the activation energy of CME is slightly higher than that of HME which means that the reactivity of the latter is higher. The bimodality that occurs in tanδ curve means that there are two phases existing in the CME and HMEA microstructure, while the secondary phase ensures that the CME and HMEA have good damping behavior. CME concrete has a better crack resistance than HMEA concrete at low temperature, and a similar crack resistance compared with HMEA concrete at high temperature. From the residual ratio of flexural stiffness after 1 million load cycles, the CME concrete shows better fatigue resistance than the HMEA concrete.